2017
DOI: 10.1007/s10552-017-0926-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sun exposure and other lifestyle variables in Swedish women

Abstract: Purpose: Sun exposure is associated with risk of several chronic diseases including cancer. The study aim is to investigate whether sun behaviours are related to other lifestyle risk factors of cancer. Results: Compared to non-drinkers, the prevalence ratio (95% CI) in women who drank >10 g of alcohol per day was 1.64 (1.49, 1.81) for having >1 sunburn per year, 1.39 (1.29, 1.51) for swimming and sunbathing >2.5 weeks per year and 1.55 (1.41, 1.70) for using a solarium >1 time per 2 months, adjusting for demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For example, a small study from Germany (n = 17) found that UVB given over 6 weeks lowered BP compared to UVA [21]. In contrast, a larger study from New Zealand (n = 119) found no differences in BP between the UVB and UVA arms after 12 weeks of intervention [22,23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, a small study from Germany (n = 17) found that UVB given over 6 weeks lowered BP compared to UVA [21]. In contrast, a larger study from New Zealand (n = 119) found no differences in BP between the UVB and UVA arms after 12 weeks of intervention [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…Data from a large Swedish study of women sampled from the community found that sun exposure behaviour is confounded by lifestyle variables: physical exercise, alcohol drinking, and tobacco smoking [22]. Furthermore, a cross-sectional study from Brazil showed age, education, and income were associated with sun exposure [24].…”
Section: Discussionmentioning
confidence: 99%